PENGARUH ROA, ROE, DAN NPM TERHADAP HARGA SAHAM PADA INDOFOOD CBP SUKSES MAKMUR TBK PADA BURSA EFEK INDONESIA PERIODE 2021-2023 - Siti Barokah; Wilson Candra Teguh Pratama; Nuriska Alfadila Zahasika Zain; Riska Tri Marlina Bisaroh (MANAJEMEN DEWANTARA, 2025)
The aim of this study is to assess the simultaneous impact of ROA, ROE, and NPM on stock prices, determining whether these variables have a positive and significant effect. The findings of the research indicate that: (1) The partial test results demonstrate that ROA has a positive and significant impact on stock prices, with a calculated t-value for ROA of 2.450 > t-table value of 2.262 and a significance value of 0.008 < 0.05. (2) The partial test results reveal that ROE has a positive and significant influence on stock prices, with a calculated t-value for ROE of 3.022 > t-table value of 2.262 and a significance value of 0.029 < 0.05. (3) The partial test results show that NPM does not have a positive and significant effect on stock prices, with a calculated t-value for NPM of 0.938 < t-table value of 2.262 and a significance value of 0.391 > 0.05. (4) The results of the simultaneous test indicate that the independent variables, which include ROA, ROE, and NPM, collectively have a positive and significant impact on stock prices, with a calculated F-value of 43.421 > F-table value of 3.633 and a significance value of 0.001 < 0.05. (5) The coefficient of determination test results show an adjusted R-squared value of 0.941 or 94.1%, meaning that the independent variables collectively explain 94.1% of the variance in stock prices, while the remaining 5.9% is influenced by other unexamined variables.